Trientine induced colitis during therapy for Wilson disease: a case report and review of the literature. Issue 1 (December 2015) - Boga, Salih; Jain, Dhanpat; Schilsky, Michael
Abstract Background Wilson disease (WD) is an autosomal recessive disorder of human copper metabolism characterized by copper accumulation in the liver due to impaired excretion of copper into the bile. Brain accumulation of copper may cause neuropsychiatric symptoms. Trientine (triethylenetetramine dihydrochloride) is a copper-chelating agent used to treat patients with WD. Trientine has been considered an option for initial treatment and maintentance therapy of WD due to its safety profile. Case presentation A 40 year old female with a recent diagnosis of WD was started on treatment with trientine for her WD. Within one month she developed profound bloody diarrhea unresponsive to medical treatment. Trientine was discontinued and a colonoscopy with biopsy showed moderately active ileitis and moderate to severe pancolitis, consistent with a drug induced mucosal injury. The colitis improved immediately upon withdrawal of trientine, and recurred when medication was rechallenged because of worsened WD symptoms. After second compulsory discontinuation of trientine, she remained on zinc therapy for her WD and her colitis resolved by time. Conclusion Drug induced colitis is a very rare side effect of trientine. Although trientine therapy is well tolerated and less side effects are reported with this medication than penicillamine, colitis can occur during trientine treatment. Zinc therapy may be an effective alternative for treatment of WD in patients experiencing side effects from chelation therapy.